2006
DOI: 10.1080/00365540500400969
|View full text |Cite
|
Sign up to set email alerts
|

Lung mass caused byPhoma exigua

Abstract: We describe a well documented case of a fatal Phoma exigua lung infection in a patient with acute myeloid leukaemia and diabetes. The infection was histology and culture proven and a PCR assay was developed for detecting P. exigua DNA in deparaffinized lung-biopsy material. Confirmation of rare fungal pathogen infections requires a multidisciplinary approach involving clinical observations, mycology, histopathology and radiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…Infection by Phoma exigua causes phaeomycotic cysts especially to vulnerable patients, leading to symptoms such as fever, painful joints, and tumors. Previous studies have reported the presence of this fungus in a diabetic ward [48]. Results from the current study and other studies indicate that diabetic patients may be the source of this organism as it was isolated in the diabetic ward only.…”
Section: Resultssupporting
confidence: 58%
“…Infection by Phoma exigua causes phaeomycotic cysts especially to vulnerable patients, leading to symptoms such as fever, painful joints, and tumors. Previous studies have reported the presence of this fungus in a diabetic ward [48]. Results from the current study and other studies indicate that diabetic patients may be the source of this organism as it was isolated in the diabetic ward only.…”
Section: Resultssupporting
confidence: 58%
“…Conidia (pycnidiospores) are produced from the phialides that line the inner wall of pycnidia and are hyaline, one‐celled, elliptical, rod shaped or curved . A PCR assay for detecting Phoma exigua DNA in deparaffinized lung biopsy material has been developed .…”
Section: Black Fungal Species With Clinical Relevancementioning
confidence: 99%
“…For the treatment of cutaneous lesions triazoles (itraconazole and voriconazole) and amphotericin B are recommended. In vitro susceptibility data on Phoma species is based on sporadic case reports with itraconazole and voriconazole MICs ranging from 0.25 to 8 mg/L and amphotericin B MICs from 0.5 to 1 mg/L .…”
Section: Black Fungal Species With Clinical Relevancementioning
confidence: 99%
“…De Hoog et al . 2000, Balis et al 2006) and other vertebrates, such as cattle (Costa et al 1993) and fish (Ross et al . 1975, Hatai et al .…”
Section: Introductionmentioning
confidence: 99%